Menanamkan Nilai Kebangsaan, Toleransi, Dan Anti-Ekstremisme Dalam PAI - Khairunnida .; Syaifuddin Sabda (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Islamic Religious Education (PAI) holds a strategic role in shaping students' morality and character amidst the challenges of globalization and the rise of extremist ideologies. This study aims to analyze the efforts to instill national values, tolerance, and anti-extremism through curricular and pedagogical transformations in PAI. Using a qualitative approach with descriptive analysis, the results indicate that national values can be integrated through Fiqh materials concerning obedience to the government and Islamic Cultural History that highlights the role of scholars in independence. Furthermore, tolerance (tasāmuh) is developed through an inclusive understanding of ukhuwah Islamiyah and religious moderation (Wasathiyyatul Islam). The success of internalizing these values heavily depends on the strategic role of PAI teachers as role models, school headmasters' policies that support an inclusive culture, and strong collaboration between schools, parents, and the community. The implementation of moderate PAI is a crucial key in building students' cognitive immunity against the appeal of radical ideologies to maintain the sovereignty of the Republic of Indonesia.